2015
DOI: 10.1093/abbs/gmv023
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish phosvitin is an antioxidant with non-cytotoxic activity

Abstract: Antioxidants, or anti-oxidant agents, have attracted a great deal of attention in recent years because of their roles in prevention of chronic diseases and utilization as preservatives in food and cosmetics. In this study, we clearly demonstrated that zebrafish recombinant phosvitin (rPv) is an antioxidant agent capable of inhibiting the oxidation of the linoleic acid, and scavenging the 2,2-diphenyl-1-picrylhydrazyl radical. We also showed that zebrafish rPv is a cellular antioxidant capable of protecting rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It could be speculated that the huge amounts of lipids carried by vtg in blood to supply oogenesis could be a source of oxidative stress for the female cardiovascular system. Also, it has been shown that vtg itself, in zebrafish, can act as an antioxidant . Oxidative stress refers to the production of toxic free radicals (e.g., reactive oxygen species) that have high tendency to bind different biological molecules such as lipids, proteins, and DNA and subsequently damage cells and tissues in the cardiovascular system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be speculated that the huge amounts of lipids carried by vtg in blood to supply oogenesis could be a source of oxidative stress for the female cardiovascular system. Also, it has been shown that vtg itself, in zebrafish, can act as an antioxidant . Oxidative stress refers to the production of toxic free radicals (e.g., reactive oxygen species) that have high tendency to bind different biological molecules such as lipids, proteins, and DNA and subsequently damage cells and tissues in the cardiovascular system.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it has been shown that vtg itself, in zebrafish, can act as an antioxidant. 33 Oxidative stress refers to the production of toxic free radicals (e.g., reactive oxygen species) that have high tendency to bind different biological molecules such as lipids, proteins, and DNA and subsequently damage cells and tissues in the cardiovascular system. Antioxidants detoxify and protect cells by binding and neutralizing such toxic compounds.…”
Section: Lipid and Other Materials Transportersmentioning
confidence: 99%
“…Other egg-related antioxidant enzymes include lysozyme, nitric oxide inhibitor cystatin, and metal-binding phosvitin (Ishikawa et al 2004;Nimalaratne and Wu 2015). Oviparous fish similarly deposit vitellogenin and phosvitin, major yolk proteins that scavenge free radicals attributable to phosphoserine protein structure and ironchelating capacity (Hu et al 2015). Redox homeostasis critically hinges on GPXs and glutathione de novo synthesis, demonstrated by localization of the enzymes in the yolk and increasing expression in critical tissues such as the brain, liver, and kidney during development (Glisic et al 2015;Mendieta-Serrano et al 2015).…”
Section: Protective Anti-ferroptotic Adaptations In the Eggmentioning
confidence: 99%
“…We also showed that zebrafish rPv is a cellular antioxidant capable of protecting radical-mediated oxidation of cellular biomolecules. Importantly, zebrafish rPv is non-cytotoxic to murine macrophages RAW264.7 [ 91 ]. These results show that Pv in fish is also a strong antioxidant agent.…”
Section: Antioxidant Activities Of Vtgs and Yolk Proteinsmentioning
confidence: 99%